Saccade Latency and Metrics in the Interleaved Pro- and Anti-Saccade Task in Open Skill Sports Athletes - Chen, Jui Tai (2024)
Evidence has demonstrated that athletes exhibit superior cognitive performance associated with executive control. In the oculomotor system, this function has been examined using the interleaved pro-saccade and anti-saccade task (IPAST), wherein participants, prior to target appearance, are instructed to either automatically look at the peripheral target (pro-saccade) or suppress the automatic response and voluntarily look in the opposite direction (anti-saccade). While the IPAST has provided much insight into sensorimotor and inhibitory processing, it has yet to be performed in athletes. Moreover, limited research has examined saccade metrics in athletes. Here, we examined saccade latency and movement kinematics in the IPAST among athletes (N = 40) and nonathletes (NON) (N = 40). Higher direction error rates were obtained in the anti-saccade compared to the pro-saccade condition, with no differences between athletes and NON noted. Significantly faster saccade latencies were observed in athletes compared to NON in both conditions, in addition to faster pro-saccades compared to anti-saccades. Furthermore, athletes showed significantly higher frequencies and faster latencies of express saccades compared to NON in correct pro-saccades. Additionally, athletes exhibited significantly faster latencies of express saccades compared to NON in erroneous anti-saccades. Differences in saccade metrics between athletes and NON were not seen. Overall, these findings demonstrate that athletes display altered saccade performance likely associated with sensorimotor and preparatory processing, highlighting the potential of using IPAST to objectively investigate sensorimotor and cognitive functions in athletes.